2014
DOI: 10.1097/01.prs.0000436840.69752.7e
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Transplantation Results in Spontaneous Lymphatic Reconnection and Restoration of Lymphatic Flow

Abstract: Background Although lymph node transplantation has been shown to improve lymphatic function the mechanisms regulating lymphatic vessel reconnection and functional status of lymph nodes remains poorly understood. Methods We developed and used LacZ lymphatic reporter mice to examine the lineage of lymphatic vessels infiltrating transferred lymph nodes. In addition, we analyzed lymphatic function, expression of vascular endothelial growth factor (VEGF-C), maintenance of T and B cell zone, and anatomic localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
2
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 20 publications
6
87
2
3
Order By: Relevance
“…Cre expression was induced in adult male mice by using tamoxifen (300 mg/kg/d subcutaneously for 5 days) followed by either systemic (100 ng i.p.) or local (5 ng subcutaneously daily ×3 doses) DT delivery (58).…”
Section: Generation Of Flt4-dtr Mice Flt4-creermentioning
confidence: 99%
“…Cre expression was induced in adult male mice by using tamoxifen (300 mg/kg/d subcutaneously for 5 days) followed by either systemic (100 ng i.p.) or local (5 ng subcutaneously daily ×3 doses) DT delivery (58).…”
Section: Generation Of Flt4-dtr Mice Flt4-creermentioning
confidence: 99%
“…Recently, Aschen et al, in an innovative experiment on an acute lymphedema model in transgenic mice, were able to show massive infiltration of recipient lymphatics into the transferred lymph nodes, spontaneous anastomosis between the recipient and donor lymphatics, and close proximity of the lymphatics to the high endothelial venules of the lymph nodes. 16 It will be interesting to see whether these results can be reproduced in a chronic lymphedema model. Table 2 3,25,30-34 summarizes study methodologies of the published clinical series on vascularized lymph node transfer.…”
Section: Functional Mechanismsmentioning
confidence: 83%
“…20,21 Other experiments have shown that expression of endogenous VEGF-C is markedly raised at the sites of lymphangiogenesis and that it can be further enhanced by induction of a sterile inflammatory response after lymph node transfer. 16,17,22 In summary, there is good evidence to suggest that avascular lymph node fragments autotransplanted into suitable recipient sites will regenerate into lymphoid tissues. Maintaining vascularization of the transferred lymph nodes ensures their survival and is essential when a lymph node-bearing block of tissue is transferred.…”
Section: Experimental Studiesmentioning
confidence: 97%
“…Nonetheless, surgery for LE must be performed in conjunction with CDT and should not be performed alone. Both treatment modalities interact positively with each other [6,48,[53][54][55][56].…”
Section: Surgical Treatment Of Lementioning
confidence: 99%